La enseñanza en el grado y la investigación del fenómeno conflicto en la Facultad de Derecho de la Universidad de Buenos Aires - Calcaterra, Rubén (2013)
The present work deals with the teaching of the conflict phenomenon at the University of Buenos Aires Law School. It aims to approach not only the contents and how it is taught, but also the state of the art research in the field and its importance as a producing cause of law. In addition it raises the challenge of integrating conflict resolution theory to law in such a way that it promotes a change over law schools curricula and in procedural rules used in the administration of justice.